Neuroprotective effect of FK506 against oxidative stress - Rosbaco, Maria Emilia (2020)
Immunophilins FKBP51 and FKBP52 bind the macrolide FK506. Previously, we reported that FK506 favours neurodifferentiation and the neuroregeneration. Here, we analyzed whether FK506 also shows neuroprotective action to oxidative stress. A rapid neuritogenesis was observed in undifferentiated N2a cells treated with 1 µM FK506 in the absence of trophic factors, including serum. Then, 250 µm slices from prefrontal cortexes from Balb-C mice (60 d) were prestabilized for 72 h and incubated for 4 h with 200 µM H2O2.